KERAGAMAN GENETIK, HERITABILITAS DAN KORELASI ANTAR KENTANG (Solanum tuberosum L.) YANG DIBUDIDAYAKAN DI NAPU - Erawati S Halide; Asri Pirade Paserang (Biology Department, Mathematics and natural science, Tadulako University, 2020)
Potato (Solanum tuberosum L.) is one of crops which cultivated by farmers in Central Sulawesi. These potatoes are traditionally cultivated without going through the breeding process, so they have high variations. This study aims to obtain information on genetic diversity, heritability, and correlation between the characterics of potatoes from farmers in Napu who are still cultivating potato crops. Design used in this study was a randomized block design with two replications. The results showed that tuber color and harvest age had a small coefficient of genetic diversity. The heritability values ​​of tuber color are include in the small category, Diameter of stem, number of leaves, leaf length, leaf width, leaf color, tuber length, tuber diameter, tuber weight, number of tuber and harvest age in this study are include in the high category. So that, these characteristics can be derived and selection can be made. In Napu potatoes, the number of tubers was genetically positively (medium) correlated between plant height and stem diameters, plant height with leaf width, leaf length with leaf width, leaf length with tuber diameters and tuber diameters with the number of tubers. While the positive correlation was very significant (strong) between plant height and leaf length, and very significant (strong) negative correlation between leaf color and tuber length, so can be used as a selection criteria for increasing potato crops.